2003
DOI: 10.1002/cphc.200300770
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Nanotubes

Abstract: Since the discovery of carbon nanotubes by lijima in 1991, various carbon nanotubes with either a single- or multilayered graphene cylinder(s) have been produced, along with their noncarbon counterparts (for example, inorganic and polymer nanotubes). These nanostructured materials often possess size-dependent properties and show new phenomena related to the nanosize confinement of the charge carriers inside, which leads to the possibility of developing new materials with useful properties and advanced devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(132 citation statements)
references
References 140 publications
0
125
0
1
Order By: Relevance
“…A wide range of approaches have been developed to synthesize CNTs including, for example, carbon arc-discharge (Ebbesen & Ajayan, 1992) and pyrolysis of hydrocarbons (Harris, 1999) for MWNTs, carbon arc-discharge (Harris, 1999), pulsed laser vaporization (Journet et al, 1997;Thess et al, 1996) and pyrolysis of hydrocarbons or carbon monoxide (Zheng et al, 2002) for SWNTs, chemical vapor deposition for aligned MWNTs (Dai, 2006;Dai et al, 2003;Harris, 1999), and plasma-enhanced chemical vapor deposition for aligned SWNTs. Depending on their diameter and helicity of the arrangement of carbon atoms in the walls, CNTs can exhibit semiconducting or metallic behavior (Dai, 2006;Harris, 1999), with an electrical conductivity as high as 5000 S/cm (Dresselhaus, 1996).…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…A wide range of approaches have been developed to synthesize CNTs including, for example, carbon arc-discharge (Ebbesen & Ajayan, 1992) and pyrolysis of hydrocarbons (Harris, 1999) for MWNTs, carbon arc-discharge (Harris, 1999), pulsed laser vaporization (Journet et al, 1997;Thess et al, 1996) and pyrolysis of hydrocarbons or carbon monoxide (Zheng et al, 2002) for SWNTs, chemical vapor deposition for aligned MWNTs (Dai, 2006;Dai et al, 2003;Harris, 1999), and plasma-enhanced chemical vapor deposition for aligned SWNTs. Depending on their diameter and helicity of the arrangement of carbon atoms in the walls, CNTs can exhibit semiconducting or metallic behavior (Dai, 2006;Harris, 1999), with an electrical conductivity as high as 5000 S/cm (Dresselhaus, 1996).…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…The catalytic growth of carbon nanotubes is currently the method of choice for growing vertically-aligned patterned arrays for a wide range of electronic, gas sensing and biological applications [1][2][3] . Significant advances in the understanding of the growth processes have generally been linked to their in-situ observation [4][5][6][7][8] , usually in specially-modified electron microscopes.…”
mentioning
confidence: 99%
“…Furthermore, the production of CNTs using the CCVD technique has been found to depend on the type of carbon source, catalyst, growth time, and growth temperature [6][7][8]. Previously, Shah and Tali [8] found that inert methane and carbon monoxide produced single-wall CNTs (SWCNTs), while Dia et al [11] and Yardimci et al [12] independently demonstrated that unsaturated hydrocarbons such as acetylene can be used for multi-walled CNT (MWCNT) growth. Similarly, Chiwaye et al [13] and Liu et al [14] concluded that acetylene gas remained the most reactive unsaturated hydrocarbon and was most frequently employed for the growth of MWCNTs.…”
Section: Methodsmentioning
confidence: 99%